The Southern Africa Development Community (SADC) endorses creation of a regional network for the conservation and use of crop wild relatives - Dulloo, Mohammad Ehsan (2021)
The Alliance led the development of a regional network for the conservation and use of Crop Wild Relatives (CWR) in the Southern African Development Community (SADC) region. This network was formally endorsed by the SADC Ministers responsible for Agriculture and Food security, Fisheries, and Aquaculture. The network will serve as a platform for CWR stakeholders (researchers, gene bank curators, breeders, conservationists and farmers) to promote effective conservation and use of CWR. On May 7, 2021, the Darwin Initiative project 26-023 achieved a milestone by gaining approval for a white paper proposing the creation of the Southern African Development Community (SADC) Crop Wild Relatives (CWR) Regional Network. This network, supported by the SADC Plant Genetic Resources Centre, is the world's first regional initiative for conserving crop wild relatives, setting an example for other regions to follow in establishing a global CWR network.